TO THE PROBLEM OF PSYCHOLOGICAL ANALYSIS OF COMPONENTS OF PROFESSIONAL IDENTITY OF STUDENTS - PSYCHOLOGISTS (Pedagogy of Higher and Secondary Education, 2011)
The article is about research of becoming of professional identity. Author cites a іегвн formation of each component of professional identity at different stages of their education the institute .
Keywords: identity; professional identity; practical psychologists; professional self-appraisal; professional values; professional satisfaction